Low Photosensitizer Dose and Early Radiotherapy Enhance Antitumor Immune Response of Photodynamic Therapy-Based Dendritic Cell Vaccination - Doix, Bastien; Trempolec, Natalia; Riant, Olivier; Feron, Olivier (Frontiers in Oncology, 2019)
Recent studies have highlighted the potential of photodynamic therapy (PDT) to induce immunogenic cell death (ICD). The clinical use of photosensitizers (PS) to stimulate an anticancer immune response, and not to sterilize tumor cells, may however require some optimizations. Here, we examined how the dose of PS and the scheduling of PDT influence the generation of danger-associated molecular patterns proteins (DAMPs) and favor T cell antitumor activity. We found that upon photoactivation, a low dose of the non-porphyrinic PS OR141 was more prone than higher doses to induce DAMPs in vitro and to inhibit squamous cell carcinoma growth in mice. We further used PDT-killed cancer cells to prime dendritic cells (DC) and stimulate their maturation to evaluate whether the timing of their injection could influence the antitumor effects of radiotherapy. While PDT-based DC vaccination administered before radiotherapy failed to increase tumor growth inhibition, DC injection in the peri-radiotherapy period led to significant tumor growth delay, emphasizing the importance of the coincidence of T cell activation and alterations of the tumor bed. In conclusion, the use of OR141 as a bona fide ICD inducer led us to unravel both the non-linear relationship between PS concentration and PDT-induced antitumor immune response, and the value of an optimal timing of PDT when co-administered with conventional anticancer therapies. This study therefore stresses the necessity of adapting the clinical use of PDT when the goal is to promote an immune response and identifies PDT-based DC vaccination as a suitable modality to reach such objective.